PENENTUAN KANDUNGAN LOGAM Pb DAN Cr PADA AIR DAN SEDIMEN DI SUNGAI AO DESA SAM SAM KABUPATEN TABANAN - DIANTARIANI, NI PUTU; DHARMA PUTRA, K.G. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 1 No 2, 2012)
Research on the heavy metal content, Pb and Cr in water and sediment of Ao River in Sam SamVillage, Tabanan Regency have been carried out. Sample of water taken at 8 location per week during 4weeks, while sample of sediment only taken once at 8 location. Determination of metal content of Pb and Crconducted using destruction method with mixture of HNO3 dan HCl (3:1) and analysed with AbsorptionAtomic Spectrophotometer.The result showed that mean metal content of Pb and Cr in water of Ao river at the location aftertextile industry (location 5 until 8) from four times intake of samples have passed enabled boundarythreshold that is 0,03 mg/L for Pb and 0,05 mg/L for Cr. Mean Pb content in sediment at location 1, 2, 3, 4and 5 still under natural content while location 6, 7 and 8 over the natural boundary threshold. Meanwhile forthe Cr metal only at location 8 over the natural boundary threshold. The highest metal content of Pb and Cr insediment and water found at location 8 that is each of 0,496 mg/L and 0,213 mg/L for Pb and Cr in water and141,844 mg/Kg and 33,489 mg/Kg for Pb and Cr in sediment respectively.